Neuroendocrine carcinomas of the breast: Case series with review of literature - Vishal Singh; Navpreet Kaur; Shramana Mandal; Varuna Mallya; Reena Tomar; Nita Khurana; Lovenish Bains (Wolters Kluwer Medknow Publications, 2020)
Background: The breast tumors with neuroendocrine differentiation show features similar to their counterparts in other organs. Neuroendorine carcinomas account for less than 0.1% of all breast carcinomas. Aims: To study the demographics and clinicopathological prameters ten cases showing neuroendocrine carcinoma breast. Material and Methods: Ten cases showing neuroendocrine carcinoma were studied. The data was analysed for demographics and clinicopathological prameters. The Immunohistochemistry for ER, PR, Her2neu, Synaptophysin, Chromogranin, NSE, Ki67 index and EMA were done in these cases. Results: Nine Trucut biopsies were reported as infiltrating duct carcinoma and one case as IDC with neuroendocrine differentiation with focal mucinous areas.The histopathological slides of breast excision specimens revealed clusters of cells arranged in sheets and small nests separated by thin fibrous septae in eight of the cases. Trabeculae were noted in two case and in another rosettes were noted. DCIS component was noted in two cases. Infiltration into fat in five of the cases. One case showed pools of mucin. The tumour cells were positive for synaptophysin in 5/10 cases, chromogranin in 8/10 cases and NSE in 9/10 cases. Estrogen receptor positivity was noted 6 cases (6/10), progesterone receptor positivity in 8 cases (8/10) and Her2neu positivity in 5 cases (5/10). Conclusion: NECB cases are more likely to ER/PR positive with variability of expression of neuroendocrine markers. These tumors are more aggressive with propensity for distant metastasis. Endocrine therapy may be more beneficial than standard chemotherapy. Anti-angiogenic markers are an exciting new approach for these case, which is yet to be explored.